2020
DOI: 10.1177/0961000620949648
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in the library: Adoption of smartphones in accessing electronic resources in a Ghanaian university

Abstract: This paper examines the influence of innovation on the adoption of smartphones for accessing electronic resources in the library by postgraduate students at the University of Cape Coast, Ghana. The theoretical model that underpinned this study was the diffusion of innovation theory. Based on a quantitative research approach, a survey research design was used. Questionnaire was employed in the collection of data from 278 postgraduate students. The responses were coded, captured and analysed using IBM’s Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…This may be in the form of a dedicated "distance education resources" Web-page on the library website with links to the distance education website and further to the learning management system. This site must also be optimised for mobile devices as students are increasingly accessing online content through their mobile devices (Adzobu et al, 2020). Also, to achieve enhanced representation for distance services, the appointment of subject librarians for discipline-specific research consultations (Chesley et al, 2020) in distance education is also recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be in the form of a dedicated "distance education resources" Web-page on the library website with links to the distance education website and further to the learning management system. This site must also be optimised for mobile devices as students are increasingly accessing online content through their mobile devices (Adzobu et al, 2020). Also, to achieve enhanced representation for distance services, the appointment of subject librarians for discipline-specific research consultations (Chesley et al, 2020) in distance education is also recommended.…”
Section: Discussionmentioning
confidence: 99%
“…This form of communication may be achieved primarily through one-way (asynchronous) such as e-mail or two-way (synchronous) such as chat or telephone services. Despite the overwhelming lack of awareness of these digital reference services, most of the distance learners singled out the e-mail as a service they were aware of, a response which was least surprising because e-mail software is common on most hand-held digital devices (Adzobu et al, 2020). Notwithstanding, from the interview with librarians, it was noted that the library does not have any form of communication service with distance learners and this includes digital reference services.…”
Section: Distance Learners' Perspectivementioning
confidence: 99%
“…According to Adzobu, Okyere [6], since the inception of the 21 st century ICT has remained the major contemporary tool shaping the global economy and producing rapid changes in society. Similarly, ICT has transformed the nature of education, where and how learning takes place and the role of students in the teaching and learning process.…”
Section: Challenges Of Use Of Information and Communication Technologmentioning
confidence: 99%
“…Studies have shown that, there are some factors that determine teachers' use and non-use of the new technologies for teaching and learning in the advanced countries and these have varying impacts on the learners. These include the needs of the learner, the characteristics and experience of teachers, the technology available, the environment within which teachers work and how valuable they perceived the use of technology for teaching their students [6,10]. It is also influenced by the subject area in which the teacher is trained [11].…”
Section: Challenges Of Use Of Information and Communication Technologmentioning
confidence: 99%
“…In light of these capabilities, many academic institutions across the globe have invested in state-of-art information technology infrastructure to minimize operational costs and improve the efficiency of academic processes. Print materials in libraries are being digitized to provide learners access to learning materials anytime and from anywhere (Adzobu et al , 2021). Per Statista (Johnson,2021), more than 50% of the world’s population is active on the Internet, mobile devices and social media.…”
Section: Introductionmentioning
confidence: 99%